Cooperative Learning in Veterinary Science (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
Cooperative learning is an instructional method based on teamwork, by reinforcing a student´s own learning as well as the learning of his or her fellow members. Thus, this kind of cooperative model achieves personal and team success at the same time. With this aim, an experience was designed where students from veterinary surgery and propaedeutics from the Universities of Las Palmas de Gran Canaria (ULPGC) and CEU Cardenal Herrera of Valencia (UCH-CEU) simultaneously performed surgical practices in the Veterinary Medicine Degree. Propaedeutic students were evaluated previously and after the practical period with surgery multiple-choice questions and results were compared. The obtained results allow us to conclude that students after interaction gained advanced knowledge in veterinary surgery.